Investigating Error in Written English Sentences: A case study Indonesia EFL Students - Ahmad Sunandar; Ratna Susanti (Basic and Applied Education Research Journal, 2020)
This research was conducted to find out the students’ gram-matical errors in writing and focused on the types of errors found in 20 writ-ten sheets of students’ descriptive text given as a part of the assignment of the second semester of Polytechnic Indonusa Surakarta majoring in Medical Records Program Study.Method: This research used qualitative research to collect empirical data from the students’ written works. Results: In this re-search, it was found that 1) in investigating types of grammatical errors in students’ written works, it can be inferred that there are 417 errors that oc-curred in students’ written works. It was found 40 types of grammatical er-rors in this study. 2) In figuring out how mother tongue interference effects on students’ written works. It was found 66 or 15.83% was caused by mother tongue interference or interlingual errors. Errors due to mother tongue in-terference were categorized into three: (i) word-by-word translation, it was found 14 or 21% errors, (ii) using Indonesian construction in English, it was counted 21 or 32%, (iii) using adjectives as main verbs, 31 or 47% errors were found. 3) In revealing why such errors occur in students’ written works. We found two general causes of errors in students’ written works. Conclu-sions: The total grammatical errors found in students’ written works were 417 errors, 351 (84.17%) errors were caused by intralingual errors, and 66 (15.83%) errors were caused by interlingual errors.